How do disadvantaged children perceive, understand and experience household food insecurity? - Velardo, S.; Pollard, Christina; Shipman, J.; Booth, S. (2021)
Food insecurity is associated with reduced physical, social, and psychological functioning in children. There has been sparse research into child food insecurity that incorporates children’s own perspectives, as adults are often interviewed as child proxies. While a nuanced, child-centred understanding of food insecurity is needed to inform effective policy and program responses, little is known about Australian children’s firsthand understanding or experience of household food insecurity. This study aimed to fill this gap by inviting preadolescent children’s perspectives. Eleven participants aged 10–13 years (seven girls and four boys) took part in the study and were recruited from an Australian charity school holiday camp that targets severely disadvantaged youth. Children took part in individual semi-structured interviews that incorporated drawings and emoji scales. Qualitative interviews were audio recorded, transcribed, and analysed using thematic techniques. Four themes emerged from the data analysis, children had: (i) financial understanding; (ii) awareness of food insecurity and coping mechanisms; (iii) sharing, empathy, and compassion for food insecure families; and (iv) described the nature of ‘food’ preparation. This study provides a child-centric analysis, demonstrating how children’s agency is enacted and constrained in food insecure contexts. This child-derived understanding of food insecurity provides a critical basis from which to build effective approaches to assess and respond to this significant social issue.